Traditional Entrepreneurship Practices : (A Study on Tharu Women of Tulsipur Sub-Metropolitan, Gaurigaun, Dang) - Lamichhane, Bhubaneshwar (Academia Research Journal, 2023)
This study highlights the extent to which cultural traditional basket entrepreneurship in the Tulsipur Sub-Metropolitan City-10; Gaurigoun of Dang District is poorly developed. A number of problems related to the production and marketing of crafts in the Dang District have been identified. The supply of handcraft was found to be less today than ten years ago in terms of quality, quantity, and variation of products. At the same time, it was observed that the commercialization of baskets only few of the traditional basket designs remain. Due to the absence of an overall national promotion scheme, the exports of crafts from the Dang District is said to be unorganized and underdeveloped. It was further noted that activities by the government geared towards craft development and marketing such as craft exhibitions has put more emphasis on basketry at the same time neglecting other crafts in the region especially craftwork. Lastly, it was mentioned that ever since the commercialization of Baskets in the Dang, natural resources have been over-utilized.